PENGARUH GAYA KEPEMIMPINAN PARTISIPATIF DAN KOMUNIKASI TERHADAP DISIPLIN KERJA GURU SDN 013 BALIKPAPAN SELATAN - jurnalmap map; Lili Erliyani Nata; Nugroho Mardi Wibowo; Cathrine Sri Hartati (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
ABSTRACT This study aims to study the participative leadership style, communication and work discipline of teachers at SDN 013 Balikpapan Selatan and to analyze participatory leadership styles and communication styles simultaneously and partially towards teacher work discipline in SDN Segugus 3 Balikpapan Kota. This study uses quantitative and explanatory types of research. The population in this study was teachers at SDN 013 Balikpapan Selatan. The study sample was a trial of 30 teachers. The sampling technique uses saturated samples. Methods of collecting data using questionnaires and documentation. Data analysis method used descriptive analysis and multiple regression analysis, F test and t test. Simultaneous and partial between participatory leadership style and communication towards the work discipline of teachers at SDN 013 Balikpapan Selatan. Participatory leadership style has a large role in the work discipline of teachers in SDN 013 Balikpapan Selatan compared to communication. Keywords: participatory leadership style, communication, work discipline